Networked operations and transformation : context and Canadian contributions - English, Allan D. (Allan Douglas), 1949- (McGill-Queen's University Press, 2007)
The authors consider various approaches to networked operations that are based on the physical environment and cultural context in which armed forces operate. They conclude that a "one size fits all" approach to command and control for networked operations may not be the most effective and suggest a more human-centric approach than the primarily technology-centred model used by the U.S. military.